2014
DOI: 10.1038/srep05171
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis-activated monocytes/macrophages cause aortic inflammation

Abstract: A relationship between periodontal disease and atherosclerosis has been suggested by epidemiological studies. Ligature-induced experimental periodontitis is an adequate model for clinical periodontitis, which starts from plaque accumulation, followed by inflammation in the periodontal tissue. Here we have demonstrated using a ligature-induced periodontitis model that periodontitis activates monocytes/macrophages, which subsequently circulate in the blood and adhere to vascular endothelial cells without alterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 46 publications
(54 reference statements)
8
62
0
1
Order By: Relevance
“…However, our findings also indicate that EP caused a slight increase in serum TNF‐α levels. Although this finding is generally compatible with those of animal studies with similar designs , some studies detected a significant increase in TNF‐α level . Human studies have reported varying results .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, our findings also indicate that EP caused a slight increase in serum TNF‐α levels. Although this finding is generally compatible with those of animal studies with similar designs , some studies detected a significant increase in TNF‐α level . Human studies have reported varying results .…”
Section: Discussionsupporting
confidence: 88%
“…In a recent study, Miyajima et al . found no significant changes in TNF‐α, CRP or IL‐6 serum levels in rats with EP. However, they found that TNF‐α and IL‐6 mRNA expression increased 2.7‐ and 2.6‐fold, respectively, in circulating mononuclear cells.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies have suggested a role for monocytes from patients with periodontitis in aortic inflammation [11,12]. These data suggested that monocytes during or after periodontal pathogen challenge could contribute to inflammation in periodontitis-associated systemic disease.…”
Section: Discussionmentioning
confidence: 82%
“…Periodontitis, an oral infectious disease predominantly by Porphyromonas gingivalis (P. gingivalis) (Darveau, 2010), has been one of the risk factors for cardiovascular diseases (Friedewald et al, 2009), by triggering the initial pathogenesis of atherosclerosis, inflammation of the vasculature, through activating monocytes/macrophages (Miyajima et al, 2014). P. gingivalis was detected in atheromatous plaques and reported to perpetuate systemic inflammation (Darveau, 2010;Kozarov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%